Carbon nanotube/polypyrrole nanocomposite as a novel cathode catalyst and proper alternative for Pt in microbial fuel cell - Ghasemi, Mostafa; Wan Daud, Wan Ramli; Hassan, Sedky H.A.; Jafary, Tahereh; Rahimnejad, Mostafa; Ahmad, Azri; Yazdi, Mohammad H. (Elsevier, 2015)
This study demonstrates the use of carbon nanotube polypyrrole (CNT/PPy) nanocomposite as a novel cathode catalyst in microbial fuel cells (MFC). The CNT/PPy nanocomposite has been prepared using a chemical oxidative method and its performance in MFC was evaluated and compared with platinum, the traditional cathode catalyst. The attachment of microorganisms on the anode was confirmed using field emission scanning electronic microscopy (FESEM) analysis. The size of ppy nanoparticles was also observed using SEM. Cyclic voltammetry (CV) studies were done to investigate the catalytic properties of CNT/PPy nanocomposite. The maximum power density and coulombic efficiency attained by the usage of CNT/PPy nanocomposite was found to be ~113 mW/m2 and 21% respectively, which is a significant comparison with the Pt catalyst, where the measured values were 122.7 mW/m2 and 24.6% respectively. The COD removal of both systems was found to be more than 80%. The results indicate that CNT/PPy nanocomposite could be used as a possible lower cost alternative than Pt catalyst in MFC.